To what extent can zero tillage lead to a reduction in greenhouse gas emissions from temperate soils? - Mangalassery, S.; Sjögersten, Sofie; Sparkes, Debbie L.; Sturrock, Craig; Craigon, Jim; Mooney, Sacha J. (Nature Publishing Group, 2014)
Soil tillage practices have a profound influence on the physical properties of soil and the greenhouse gas (GHG) balance. However there have been very few integrated studies on the emission of carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) and soil biophysical and chemical characteristics under different soil management systems. We recorded a significantly higher net global warming potential under conventional tillage systems (26–31% higher than zero tillage systems). Crucially the 3-D soil pore network, imaged using X-ray Computed Tomography, modified by tillage played a significant role in the flux of CO2 and CH4. In contrast, N2O flux was determined mainly by microbial biomass carbon and soil moisture content. Our work indicates that zero tillage could play a significant role in minimising emissions of GHGs from soils and contribute to efforts to mitigate against climate change.